Tuntaskan hambatan belajar dengan Pemberian Asesmen DCM di SMA NEGERI 2 TUALANG - Mahdum Mahdum; Bening Muthmainnah; Desi Belanda Situmeang; Dea Safitri; Nabila Nabila; Iffah Syahna Khalishah; Nurlaila Habibah Ahmad; Meliza Ananda (CV. ALIM'SPUBLISHING, 2024)
The article titled “Tuntaskan hambatan belajar dengan Pemberian Asesmen DCM di SMA NEGERI 2 TUALANG” discusses effective strategies for addressing learning obstacles in that school. The main focus of this article is on the implementation of the DCM as a tool to understand, identify, and address students’ learning difficulties at SMA NEGERI 2 TUALANG. The research demonstrates that using DCM can enhance students’ motivation toward the material and reduce learning challenges. The research methodology involves data collection through observation, interviews, and analysis of test results before and after DCM implementation. The findings indicate that students who receive DCM assessments show significant improvement when provided with group counseling services. The article provides practical recommendations for teachers and schools to utilize DCM assessments as a tool to enhance learning quality and reduce learning barriers within the school context.